Dark enlightenment : The Historical, sociological, and discursive contexts of contemporary esoteric magic - Granholm, Kennet, 1977- (Aries Book Series, 2014)
In Dark Enlightenment Kennet Granholm explores the historical, sociological, and discursive contexts of contemporary esoteric magic. The book is focused on the Sweden-originated Left-Hand Path magic order Dragon Rouge in particular, but through a detailed contextualizing examination of this case study it offers a broader visage of contemporary esotericism in general. The author takes cue from both the historiography of Western esotericism and the sociological study of new religions and religious change, aiming to provide a transdisciplinary framework for a comprehensive study of esotericism in late modernity.